Observation of B → φK and B → φK - Briere, R; Chen, G; Ferguson, T; Vogel, H; Gritsan, A; Alexander, J; Baker, R; Bebek, C; Berger, B; Berkelman, K; Blanc, F; Boisvert, V; et al. (2001)
An overview is given on the first significant measurements of exclusive charmless hadronic decays B → φK and B → φK*. The measured branching fractions lie in the range of theoretical predictions.